2018
DOI: 10.1039/c7ra13423a
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic extraction of dysprosium and thermodynamic evaluation of Cu–Dy intermetallic compound in eutectic LiCl–KCl

Abstract: The electrochemical reduction of dysprosium(iii) was studied on W and Cu electrodes in eutectic LiCl–KCl by transient electrochemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…After DyCl 3 was added to the molten salt, a new pair of redox peaks shown in red line, II/II' (−2.02/−1.80 V), was observed, which is attributed to the formation and dissolution of Dy metal. [ 43 ] When ZnCl 2 was added to LiCl–KCl, the redox peaks III/III', in blue, were detected, which are attributed to the deposition and oxidation of Zn metal. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After DyCl 3 was added to the molten salt, a new pair of redox peaks shown in red line, II/II' (−2.02/−1.80 V), was observed, which is attributed to the formation and dissolution of Dy metal. [ 43 ] When ZnCl 2 was added to LiCl–KCl, the redox peaks III/III', in blue, were detected, which are attributed to the deposition and oxidation of Zn metal. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] Molten salt electrochemical formation of alloys was investigated as they have many advantages. [ 35 ] Therefore, the electrochemical behaviors and formation of Dy alloys on reactive electrodes Al, [ 4,36 ] Bi, [ 5 ] Fe, [ 37,38 ] Ni, [ 39–42 ] Cu, [ 43 ] Sn, [ 30 ] and Mg [ 44 ] were explored in different molten salt systems, and it was found that the metal Dy can form different Dy–M (M = Al, Bi, Fe, Ni, Cu, Sn, and Mg) alloys and Dy can be extracted on reactive electrodes. However, the electrochemical properties of Dy and the formation of Dy–Zn alloys have not yet been fully explored on Zn electrode.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts. 29 In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, for example, Mg, 30 Al, [31][32][33][34] Ni, 35,36 Cu, [37][38][39] Bi, [40][41][42][43] Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, [49][50][51] and Ga. 52 Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode. Our group investigated the electroextraction of Tb and Y from molten chloride using solid Cu and liquid Zn as working electrodes and found that under same conditions, metallic Y and Tb easily deposited on liquid Zn electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction activation energy for the Dy(III)/Cu 5 Dy couple was found to be higher than that for the Dy(III)/Cu 9/2 Dy couple. 38 Metallic yttrium is one of ssion products. Many investigators selected it as a representative rare earth element to study the electrochemical extraction on diverse electrodes.…”
Section: Introductionmentioning
confidence: 99%